Minority languages and multilingual education - Gasparini, Nathália; Viégas, Maiara (Domínios de Lingu@gem, 2016)
Resenha da obraGORTER, Durk; ZENOTZ, Victoria; CENOZ, Jasone (Eds.). Minority languages and multilingual education: Bridging the local and the global. Nova York: Springer, 2014.